(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
Small livestock, poultry, rabbit and fish farms are growing in our country. Based on this, for the rapid development of farms, there is a need to strengthen the feed base and the necessary equipment for preparing feed. Based on this, research is being carried out on the development of small-tonnage granulators for the development of fisheries, poultry farming, livestock farming and rabbit farming. The article has developed an experimental copy of a granulator device and presents the effect of the working parts on the granule, the results obtained and conclusions.